Early Breastfeeding Initiation of Postpartum Hemorrhage Events - Ike Putri Setyatama; Ika Esti Anggraeni (JURNAL KEBIDANAN, 2019)
Hemorrhage was the main cause of maternal mortality in Tegal, 2017. Based on the survey at Puskesmas Slawi in January-December 2018, 30 women gave birth and experienced postpartum hemorrhage. Early breastfeeding helps to reduce hemorrhage and shrink uterus after birth. The research analyzed the effect of Early Initiation of Breastfeeding towards postpartum hemorrhage at Puskesmas Slawi. The population was 215 women who gave birth at Puskesmas Slawi in January-December 2018 with 140 samples. The research design applied case control study. Based on Chi Square with α = 0.05, p value was 0.048. It means that there was a relationship in both variables. As the result of logistic regression test, Sig. value was 0.029 stating that there was an effect of those variables. OR value was 2.495 meaning that mothers who performed early initiation of breastfeeding were 2.5 times lower risk at postpartum hemorrhage than those who did not act early initiation of breastfeeding. Asymp. Sig (2-Sided) was 0.032 describing that it represented population.Thus, there were a relationship and an effect of Early Initiation of Breastfeeding towards postpartum hemorrhage at Puskesmas Slawi.